Preparation method and application of polycrystalline molybdenum carbide / cadmium sulfide composite catalyst

By preparing polycrystalline carbonized molybdenum/cadmium sulfide composite optical catalysts, carbonized molybdenum polycrystalline heresy structure is used to promote carrier transfer and electron-floor-to-ground separation, solve the problem of low existing photocatalyst efficiency, and achieve efficient light Catalytic breakdown of hydrogen.

CN119368210AInactive Publication Date: 2025-01-28EAST CHINA UNIV OF SCI & TECH

Patent Information

Application Number
CN202411556975.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-01-28
Estimated Expiration
Not applicable · inactive patent

Smart Images

  • Figure CN119368210A_ABST
    Figure CN119368210A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of a polycrystalline molybdenum carbide / cadmium sulfide composite catalyst. The material has excellent performance in the aspect of hydrogen production by photocatalytic decomposition of water. The preparation method comprises the following steps: firstly, taking melamine, cyanuric acid and ammonium molybdate as raw materials, and annealing in an inert atmosphere in a tubular furnace to prepare polycrystalline molybdenum carbide; then taking cadmium nitrate, thiourea and ethidene diamine as raw materials to hydrothermally prepare cadmium sulfide in a polytetrafluoroethylene high-pressure reaction kettle; and finally, dispersing the polycrystalline molybdenum carbide and cadmium sulfide in N, N-dimethylformamide, and carrying out ultrasonic treatment, stirring, washing and drying to obtain the polycrystalline molybdenum carbide / cadmium sulfide. According to the polycrystalline heterostructure disclosed by the invention, a channel for directionally and rapidly transferring current carriers is constructed, the separation of electron-hole pairs is accelerated, and the migration rate of electrons is improved; meanwhile, a molybdenum vacancy located at a crystal boundary forms a Lewis acid site serving as an active site of a hydrogen production reaction, so that an energy barrier of the hydrogen production reaction is reduced, and excellent performance of photocatalytic decomposition of water to produce hydrogen is shown.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method of a polycrystalline molybdenum carbide / cadmium sulfide composite catalyst and its application in photocatalytic water decomposition to produce hydrogen, belonging to the field of functional technical materials. Background Art

[0002] Energy shortage and environmental pollution have become two major constraints on the development of the current era. Hydrogen energy has attracted much attention due to its high calorific value and pollution-free characteristics. However, most of the current hydrogen production comes from non-renewable fossil energy, which will inevitably bring a large amount of carbon emissions. Photocatalytic water decomposition to produce hydrogen is undoubtedly the best choice for achieving zero-carbon hydrogen production. Photocatalytic water decomposition to produce hydrogen can use inexhaustible solar energy to decompose water to produce hydrogen. Semiconductor photocatalysts absorb a certain amount of light energy, and the electrons on the valence band are excited to the conduction band to reduce hydrogen protons to generate hydrogen, and the corresponding holes left on the conduction band undergo oxidation reactions. However, the existing photocatalysts have poor practical application effects due to the rapid recombination of carriers, slow interface dynamics, and limited active sites. Therefore, the development of high-performance photocatalysts remains the focus of current research.

[0003] Cadmium sulfide is a widely existing metal sulfide with a suitable energy band structure. It can show significant photocatalytic hydrogen production activity under visible light irradiation and has a low preparation cost. It is a photocatalyst with great development potential. However, cadmium sulfide has obvious photocorrosion phenomenon, and electrons and holes are very easy to recombine, which seriously affects its photocatalytic activity. By loading co-catalysts, the directional transfer of carriers can be accelerated, providing more active sites, and further improving the efficiency of photocatalytic hydrogen production. Summary of the invention

[0004] The present invention provides a preparation method and application of a polycrystalline molybdenum carbide / cadmium sulfide composite photocatalyst, and the material can realize high-performance photocatalytic decomposition of water to produce hydrogen. Polycrystalline molybdenum carbide is prepared by an annealing method, and a cadmium sulfide photocatalyst is prepared by a hydrothermal method, and then the two are composited to obtain a polycrystalline molybdenum carbide / cadmium sulfide photocatalyst. The presence of a polycrystalline heterostructure of molybdenum carbide as a co-catalyst promotes the directional and rapid transfer of carriers, accelerates the separation of electron-hole pairs, and increases the migration rate of electrons. In addition, the presence of a large number of molybdenum vacancies increases the active sites of the hydrogen production reaction, improves the photocatalytic activity of the composite catalyst, and contributes to the optimized design, development and application of the photocatalyst.

[0005] Based on the above purpose, the technical solution adopted by the present invention is as follows:

[0006] In a first aspect, the present invention provides a method for preparing a polycrystalline molybdenum carbide / cadmium sulfide composite photocatalyst, and the specific preparation steps are as follows:

[0007] S1: Add melamine, cyanuric acid and ammonium molybdate into water and stir and disperse them, stir at room temperature, wash, separate solid and liquid, and dry to obtain a polycrystalline molybdenum carbide precursor. Grind the polycrystalline molybdenum carbide precursor and calcine it in an inert gas in a tube furnace. Grind it after natural cooling to obtain polycrystalline molybdenum carbide.

[0008] S2: Add cadmium nitrate and thiourea into an organic solvent, stir and disperse them, put the mixed solution into a polytetrafluoroethylene autoclave for solvent thermal treatment, wash, centrifuge, take the precipitate, and dry to obtain cadmium sulfide.

[0009] S3: a certain amount of polycrystalline molybdenum carbide prepared in S1 and cadmium sulfide prepared in S2 are dispersed in an organic solvent, and polycrystalline molybdenum carbide / cadmium sulfide is obtained after stirring at room temperature, washing and drying.

[0010] Preferably, the ratio of the amount of melamine, cyanuric acid and ammonium molybdate in S1 is 20:20:1. The inert gas in the tube furnace is argon, the calcination temperature is 700°C, the calcination time is 3h, and the heating rate is 2°C / min.

[0011] Preferably, the mass ratio of cadmium nitrate to thiourea in S2 is 1:1.

[0012] Preferably, the organic solvent in S2 is ethylenediamine, the volume of ethylenediamine is 60 mL, the solvent thermal temperature is 160° C., and the solvent thermal time is 48 h.

[0013] Preferably, the organic solvent in S3 is N,N-dimethylformamide, and the mass ratio of polycrystalline molybdenum carbide to cadmium sulfide is 1:10.

[0014] In a second aspect, the present invention provides a polycrystalline molybdenum carbide / cadmium sulfide prepared by the above method, which contains molybdenum (Mo) vacancies.

[0015] In a third aspect, the present invention seeks to protect the application of the above-mentioned polycrystalline molybdenum carbide / cadmium sulfide composite photocatalyst in the photocatalytic decomposition of water to produce hydrogen.

[0016] The beneficial effects of the present invention are as follows:

[0017] (1) After polycrystalline molybdenum carbide and cadmium sulfide are combined, a rapid carrier transfer channel from cadmium sulfide to polycrystalline molybdenum carbide is constructed. Electrons are quickly transferred to the grain boundaries of polycrystalline molybdenum carbide, accelerating the separation of electron-hole pairs. At the same time, the molybdenum vacancies on the grain boundaries induce electron rearrangement, causing the electrons to eventually gather on the molybdenum vacancies, participate in the water reduction reaction, and accelerate the hydrogen production reaction. Compared with single cadmium sulfide, loading polycrystalline molybdenum carbide effectively improves the efficiency of photocatalytic hydrogen production.

[0018] (2) Mo vacancies on the grain boundaries of polycrystalline MoC can form Lewis acidic sites, further reducing the energy barrier of the hydrogen production reaction.

[0019] (3) Compared with single-crystalline MoC, polycrystalline MoC can optimize the electronic structure of the material, thereby inducing rapid directional transfer of charge carriers and improving catalytic performance.

[0020] (4) The raw materials involved in the present invention are cheap and easily available, the operation method is simple, the catalyst output is considerable, and it is environmentally friendly and economical. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 TEM images of αβ-MC and αβ-MC / CS

[0022] Figure 2 .XRD patterns of α-MC, αβ-MC, β-MC, α-MC / CS, αβ-MC / CS, β-MC / CS

[0023] Figure 3 EPR diagrams of α-MC, αβ-MC, and β-MC

[0024] Figure 4 .XPS S2p images of CS, αβ-MC / CS

[0025] Figure 5 .Hydrogen production rate diagram of CS, α-MC / CS, αβ-MC / CS, β-MC / CS DETAILED DESCRIPTION

[0026] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be understood by those skilled in the art that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The test methods used in the examples are conventional methods unless otherwise specified; the materials, reagents, etc. used can be obtained from commercial sources unless otherwise specified.

[0027] Example 1

[0028] This embodiment provides a method for preparing a polycrystalline molybdenum carbide / cadmium sulfide αβ-MC / CS composite photocatalyst, comprising the following steps:

[0029] (1) Use an electronic balance to accurately weigh 10mmol (1.2612g) of melamine, 10mmol (1.2908g) of cyanuric acid and 0.5mmol (0.6179g) of ammonium molybdate, add them to 40mL of deionized water, stir and disperse, place them on a magnetic stirrer, stir at room temperature for 12h, wash, separate the solid and liquid, and dry at 80°C to obtain a polycrystalline molybdenum carbide precursor. After grinding the polycrystalline molybdenum carbide precursor, place it in a tube furnace in an argon atmosphere and calcine it at a calcination temperature of 700°C, a calcination time of 3h, and a heating rate of 2°C / min. After natural cooling, grind it to obtain polycrystalline molybdenum carbide, named αβ-MC.

[0030] (2) Add 4.62 g of cadmium nitrate and 4.62 g of thiourea to 60 mL of ethylenediamine and stir to disperse. Place the mixed solution in a 100 mL steel autoclave lined with polytetrafluoroethylene and heat in an oven at 160°C for 24 hours. Wash with deionized water and anhydrous ethanol three times respectively, set the centrifuge speed to 8000 rpm, and centrifuge for 1 min to perform centrifugal solid-liquid separation operation, and collect the precipitate. The obtained precipitate is vacuum dried at 60°C overnight to obtain cadmium sulfide, named CS.

[0031] (3) Disperse 10 mg of αβ-MC and 100 mg of CS in 10 mL of N,N-dimethylformamide and stir at room temperature for 24 h. Wash with deionized water and anhydrous ethanol three times respectively, set the centrifuge speed to 8000 rpm, and centrifuge for 1 min to perform centrifugal solid-liquid separation operation, and collect the precipitate. The obtained precipitate is vacuum dried at 60°C overnight to obtain polycrystalline molybdenum carbide / cadmium sulfide, named αβ-MC / CS.

[0032] Comparative Example 1

[0033] This comparative example provides a method for preparing a single crystal molybdenum carbide / cadmium sulfide α-MC / CS composite photocatalyst, comprising the following steps:

[0034] (1) Use an electronic balance to accurately weigh 10mmol (1.2612g) of melamine, 10mmol (1.2908g) of cyanuric acid and 0.5mmol (0.6179g) of ammonium molybdate, add them to 40mL of deionized water, stir and disperse, place them on a magnetic stirrer, stir at room temperature for 12h, wash, separate the solid and liquid, and dry at 80℃ to obtain a polycrystalline molybdenum carbide precursor. After grinding the polycrystalline molybdenum carbide precursor, place it in a tube furnace in an argon atmosphere and calcine it at a calcination temperature of 650℃, a calcination time of 3h, and a heating rate of 2℃ / min. After natural cooling, grind it to obtain polycrystalline molybdenum carbide, named α-MC.

[0035] (2) Add 4.62 g of cadmium nitrate and 4.62 g of thiourea to 60 mL of ethylenediamine and stir to disperse. Place the mixed solution in a 100 mL steel autoclave lined with polytetrafluoroethylene and heat in an oven at 160°C for 24 hours. Wash with deionized water and anhydrous ethanol three times respectively, set the centrifuge speed to 8000 rpm, and centrifuge for 1 min to perform centrifugal solid-liquid separation operation, and collect the precipitate. The obtained precipitate is vacuum dried at 60°C overnight to obtain cadmium sulfide, named CS.

[0036] (3) Disperse 10 mg of α-MC and 100 mg of CS in 10 mL of N,N-dimethylformamide and stir at room temperature for 24 h. Wash with deionized water and anhydrous ethanol three times respectively, set the centrifuge speed to 8000 rpm, and centrifuge for 1 min to perform centrifugal solid-liquid separation operation, and collect the precipitate. The obtained precipitate is vacuum dried at 60°C overnight to obtain polycrystalline molybdenum carbide / cadmium sulfide, named α-MC / CS.

[0037] Comparative Example 2

[0038] This comparative example provides a method for preparing a single-crystal molybdenum carbide / cadmium sulfide composite photocatalyst, comprising the following steps:

[0039] (1) Use an electronic balance to accurately weigh 10mmol (1.2612g) of melamine, 10mmol (1.2908g) of cyanuric acid and 0.5mmol (0.6179g) of ammonium molybdate, add them to 40mL of deionized water, stir and disperse, place them on a magnetic stirrer, stir at room temperature for 12h, wash, separate the solid and liquid, and dry at 80°C to obtain a polycrystalline molybdenum carbide precursor. After grinding the polycrystalline molybdenum carbide precursor, place it in a tube furnace in an argon atmosphere and calcine it at a calcination temperature of 750°C, a calcination time of 3h, and a heating rate of 2°C / min. After natural cooling, grind it to obtain polycrystalline molybdenum carbide, named β-MC.

[0040] (2) Add 4.62 g of cadmium nitrate and 4.62 g of thiourea to 60 mL of ethylenediamine and stir to disperse. Place the mixed solution in a 100 mL steel autoclave lined with polytetrafluoroethylene and heat in an oven at 160°C for 24 hours. Wash with deionized water and anhydrous ethanol three times respectively, set the centrifuge speed to 8000 rpm, and centrifuge for 1 min to perform centrifugal solid-liquid separation operation, and collect the precipitate. The obtained precipitate is vacuum dried at 60°C overnight to obtain cadmium sulfide, named CS.

[0041] (3) Disperse 10 mg of β-MC and 100 mg of CS in 10 mL of N,N-dimethylformamide and stir at room temperature for 24 h. Wash with deionized water and anhydrous ethanol three times respectively, set the centrifuge speed to 8000 rpm, and centrifuge for 1 min to perform centrifugal solid-liquid separation operation, and collect the precipitate. The obtained precipitate is vacuum dried at 60°C overnight to obtain polycrystalline molybdenum carbide / cadmium sulfide, named β-MC / CS.

[0042] Comparative Example 3

[0043] This comparative example provides a method for preparing a cadmium sulfide CS photocatalyst, comprising the following steps:

[0044] 4.62 g of cadmium nitrate and 4.62 g of thiourea were added to 60 mL of ethylenediamine and stirred to disperse. The mixed solution was placed in a 100 mL steel autoclave lined with polytetrafluoroethylene and heated in an oven at 160 ° C for 24 hours. It was washed three times with deionized water and anhydrous ethanol respectively, and the centrifuge speed was set to 8000 rpm and the centrifugal time was 1 min for centrifugal solid-liquid separation operation to collect the precipitate. The obtained precipitate was vacuum dried at 60 ° C overnight to obtain cadmium sulfide, named CS.

[0045] Experiments and data

[0046] The performance analysis method of the photocatalytic decomposition of water to produce hydrogen provided by the present invention is as follows:

[0047] Specifically, 20 mg of catalyst, 90 mL of deionized water and 10 mL of lactic acid were added to the reactor. Argon was used as the carrier gas, and the condensed water temperature was maintained at 5°C. A 300W xenon lamp with an AM1.5 filter was used as the light source. Samples were taken every 15 minutes, and the collected hydrogen was monitored by a gas chromatograph. The reaction time was 2 hours.

[0048] Figure 1 TEM images of polycrystalline molybdenum carbide αβ-MC and polycrystalline molybdenum carbide / cadmium sulfide αβ-MC / CS. αβ-MC is granular, cadmium sulfide CS is rod-shaped, and the final composite material αβ-MC / CS is a rod-shaped structure supported by particles.

[0049] Figure 2 The XRD patterns of the samples prepared in Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 are shown. The polycrystalline molybdenum carbide αβ-MC contains characteristic peaks of two crystalline phases, α-MoC and β-Mo2C, which can correspond well to α-MoC (PDF#89-2868) and β-Mo2C (PDF#35-0787). In addition, the characteristic peaks of single-crystalline molybdenum carbide α-MC and single-crystalline molybdenum carbide β-MC can correspond well to α-MoC (PDF#89-2868) and β-Mo2C (PDF#35-0787), respectively. The characteristic peaks of polycrystalline molybdenum carbide / cadmium sulfide αβ-MC / CS can correspond well to CdS (PDF#41-1049).

[0050] Figure 3 The EPR spectra of the samples prepared in Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3. g = about 1.92 corresponds to Mo vacancies. It proves the existence of Mo vacancies in single-crystalline molybdenum carbide α-MC, polycrystalline molybdenum carbide αβ-MC, and single-crystalline molybdenum carbide β-MC. Among them, polycrystalline molybdenum carbide αβ-MC has the strongest EPR signal, has more Mo vacancies, and contains the most active sites.

[0051] Figure 4The XPS S2p spectra of the sample and cadmium sulfide prepared in Example 1. It can be seen that after the polycrystalline molybdenum carbide αβ-MC is composited with cadmium sulfide CS, S2p moves to a higher field, indicating that electrons are transferred from CS to αβ-MC, which increases the migration rate of carriers.

[0052] Figure 5 The hydrogen production rate diagram of the samples prepared in Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3. It can be seen that the polycrystalline molybdenum carbide / cadmium sulfide αβ-MC / CS composite material has the best hydrogen production performance compared to single crystal molybdenum carbide / cadmium sulfide (α-MC / CS, β-MC / CS) and cadmium sulfide CS, and can reach a hydrogen production of 66.51 mmol / g / h, which is 33 times that of pure cadmium sulfide, and 2.28 and 1.33 times that of single crystal molybdenum carbide / cadmium sulfide α-MC / CS and β-MC / CS.

[0053] Although the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as limiting the present invention.

Claims

1. A method for preparing a polycrystalline molybdenum carbide / cadmium sulfide composite catalyst, characterized in that: The following steps are involved: S1: adding melamine, cyanuric acid and ammonium molybdate into water and stirring and dispersing them, stirring at room temperature, washing, solid-liquid separation and drying to obtain a polycrystalline molybdenum carbide precursor; grinding the polycrystalline molybdenum carbide precursor and calcining it in an inert gas in a tube furnace, and grinding it after natural cooling to obtain polycrystalline molybdenum carbide; S2: adding cadmium nitrate and thiourea to an organic solvent, stirring and dispersing them, placing the mixed solution into a polytetrafluoroethylene autoclave for solvent thermal treatment, washing, centrifuging, taking a precipitate, and drying to obtain cadmium sulfide; S3: a certain amount of polycrystalline molybdenum carbide prepared in S1 and cadmium sulfide prepared in S2 are dispersed in an organic solvent, and polycrystalline molybdenum carbide / cadmium sulfide is obtained after stirring at room temperature, washing and drying.

2. The method for preparing the polycrystalline molybdenum carbide / cadmium sulfide composite catalyst according to claim 1, characterized in that: The molar ratio of melamine, cyanuric acid and ammonium molybdate in S1 is 20:20:1; the inert gas in the tubular furnace is argon, the calcination temperature is 650-750°C, the calcination time is 3±1h, and the heating rate is 2±1°C / min.

3. The method for preparing the polycrystalline molybdenum carbide / cadmium sulfide composite catalyst according to claim 1, characterized in that: The mass ratio of cadmium nitrate to thiourea in S2 is 1:0.8 to 1:1.

2.

4. The method for preparing the polycrystalline molybdenum carbide / cadmium sulfide composite catalyst according to claim 1, characterized in that: The organic solvent in S2 is ethylenediamine, the volume of ethylenediamine is 55-65 mL, the solvent thermal temperature is 150-170° C., and the solvent thermal time is 46-50 h.

5. The method for preparing the polycrystalline molybdenum carbide / cadmium sulfide composite catalyst according to claim 1, characterized in that: The organic solvent in S3 is N,N-dimethylformamide, and the mass ratio of the polycrystalline molybdenum carbide to cadmium sulfide is 1:8 to 1:

12.

6. A polycrystalline molybdenum carbide / cadmium sulfide composite catalyst, characterized in that: The composite material is prepared by the preparation method according to any one of claims 1 to 5, and the polycrystalline molybdenum carbide / cadmium sulfide contains Mo vacancies.

7. Application of a polycrystalline molybdenum carbide / cadmium sulfide composite catalyst in the photocatalytic decomposition of water to produce hydrogen, characterized in that: The composite material is prepared by the preparation method according to any one of claims 1 to 5, and the polycrystalline molybdenum carbide / cadmium sulfide contains Mo vacancies.

Citation Information

Patent Citations

  • Mo2C cocatalyst with lamellar structure as well as preparation and application thereof

    CN111468151A

  • Acanthosphere-shaped Mo2C / CdS photocatalyst as well as preparation method and photocatalysis method thereof

    CN112619679A

  • Molybdenum carbide catalyst doped with double metals in different crystal forms

    CN118407083A

Cited By

  • Preparation method and application of highly crystallized cadmium sulfide photocatalyst

    CN120305985A